ECLAMPSIA. MATERNAL AND PERINATAL MORTALITY. CAYETANO HEREDIA HOSPITAL. JULY 1991-DECEMBER 1997 - Román Pilco, Carlos (2015)
OBJETIVE: determine maternal and perinatal mortality in eclampsia at Cayetano Heredia National Hospital between July 1991 and December 1997 MATERIAL AND METHODS: Propective and descriptive study evaluating 113 eclampsia cases RESULTS: Se 4,09% of incidence of eclampsia with major number of cases in the primigravidas group (64,6%) and in the group below, 20 years old (36,3%,), with a high percentage o preterm birth (49,5%) and cesarean section (85%) a perinatal mortality of 20 cases (17,4%), 69% of small for gestational age newborns and 36,5%, low Apgar newborns. Among the eclampsia patients 9 (8%) died because of acute renal failure, cerebral damage and Hellp syndrome. CONCLUSIÓN: Eclampsia occasioned a high maternal and perinatal mortality.